Review on “Reich of the black sun. Nazi secret weapons & the cold war allied legend” by Joseph P. Farrell - Malugin Sergey Borisovich (Studia Humanitatis, 2013)
Joseph Farrell thinks that during World War II Nazi Germany has created and successfully tested, and could have even used the plutonium bomb in a combat situation. Also it is likely that German scientists managed to make a significant step towards the creation – if not the testing – of a bomb constructed by a method of accelerated division, a bomb that has a small critical mass and a great devastating effect. This statement, however radical it may seem, in author’s opinion, can resolve many inconsistencies and contradictions in political and strategic history of the war.